ANALISIS TITIK PULANG POKOK USAHA BUDIDAYA LEBAH MADU âJAYA MAKMURâ DI DESA JONO OGE KECAMATAN SIGI BIROMARU KABUPATEN SIGI - Anggraini, Ayu Dwi; Kassa, Saharia; Laapo, Alimudin (AGROTEKBIS, 2016)
This research was supposed to know amount of acquired profit and expended cost, to know a number of manufactured products and acquired income at breaking event point, and to know margin of safety therefore honey bee farming âJaya Makmurâ still got some profits. This research was coducted at honey bee farming âJaya Makmurâ in Jono Oge village, District of Sigi Biromaru, and Regency of Sigi on June to July 2015. Respondens are consisted of two person; they are Â  the owner and the employee of honey bee farmingÂ  âJaya Makmurâ were: (1) the acquired incomes of honey bee farming âJaya Makmurâ were: (a) for product of honey 850mg in amount ofÂ  IDR 2.860.000/mount with production cost IDR 1.684.267/mount which generated profit in amount of IDR 1.175.733/mount. (b) for product of honey 400mg in amount of IDR 3.055.000/mount with production cost IDR 1.699.130/mount which generated profit in amount of IDR 1.355.870/mount. (2) the break event point for product of honey 850mg were achieve at production volume in total number 111 bottles with the price in amount of IDR 130.000/bottle, thus, the value of acquired income was IDR 1.430.000/mount. The break event point for product of honey 4050mg were achieve at production volume in total number 23 bottles with the price in amount of IDR 65.000/bottle the value of acquired income was IDR 1.495.000/mount. (3) margin of safety Â for product of honey 850mg was amount of 50.00% and for product of honey 450mg was in amount of 51.06%, which meant the maximum limited distance of decreasing sell of the second selling product was in ratio of MoS, therefore during the selling product was not decreased more than ratio MoS that meant this cultivation receive some profit.Â Key Words: Analysis of break event point, honey bee farming, Jono Oge Viilage.Â